2017
DOI: 10.1016/j.ejogrb.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Electrohysterography for uterine monitoring during term labour compared to external tocodynamometry and intra-uterine pressure catheter

Abstract: Electrohysterography has a higher sensitivity for uterine contraction detection than external tocodynamometry during first stage of labour, in non-obese and obese women. Electrohysterography identifies more contractions than conventional techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…However, visual assessment of the remaining 2 registrations showed high agreement, in both first and second stages of labor. Previous research has shown that the EHG technology performs better than TOCO during the first stage of labor in non‐obese and obese women 15 . Furthermore, the technology is preferred by women compared with conventional technologies for UA monitoring 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, visual assessment of the remaining 2 registrations showed high agreement, in both first and second stages of labor. Previous research has shown that the EHG technology performs better than TOCO during the first stage of labor in non‐obese and obese women 15 . Furthermore, the technology is preferred by women compared with conventional technologies for UA monitoring 29 …”
Section: Discussionmentioning
confidence: 99%
“…Due to the rare reported risks of the IUPC, it is not routinely applied during labor and in some hospitals only used on indication 13,14 . As the EHG algorithm incorporated in this NI‐fECG device is an improved version of a previously validated technology, 15 we believe that this limited number of IUPC registrations would be sufficient for validation of contraction monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size of 52 patients was based on a power analysis to validate the sensitivity of EHG, reported in our previous publication. 5 We used SPSS (Statistical Package for Social Science) 23 statistics (IBM, New York, USA) for statistical evaluation. Descriptive statistics included frequencies with percentages and 95% confidence intervals (CI) for categorical data, 12 13 mean with standard deviation (SD) for normally distributed continuous variables, or median with interquartile range (IQR) for nonnormally distributed continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…These techniques are compared in several studies that mainly focus on diagnostic values, interpretability, and labor outcomes. 1 2 3 4 5 Only 1 article describes patients' and users' (i.e., healthcare provider) satisfaction of 2 securing methods (belts), both concerning external TOCO devices. 6 Reports on users' and patients' preferences of all 3 uterine monitoring methods are still missing, while this topic is becoming more important nowadays.…”
mentioning
confidence: 99%
See 1 more Smart Citation